Pemenuhan Hak Pendidikan Bagi Anak Sebagai Warga Binaan Pemasyarakatan Di Lembaga Pembinaan Khusus Anak Kelas II Pangkalpinang - Rasta Buana, Syahfa Rizi; Toni, Toni; Agustian, Rio Armanda (JURNAL PENELITIAN SERAMBI HUKUM, 2025)
The regulation of the right to education for citizens has been included in the constitution, which is a form of guarantee of legal certainty and state recognition of the right to education for citizens. This study aims to review the extent to which regulations related to the right to education for fostered children have been implemented in LPKA Pangkalpinang to ensure that human rights can be fulfilled optimally. The type of research used is empirical juridical, through a sociological juridical approach. The results of the research, The fulfillment of the right to education at LPKA Class II Pangkalpinang has been implemented quite well even though the formal education program still cannot be fulfilled because there is no school that can be used as a parent, the absence of formal education shows that there is a gap in the fulfillment of the right to education as mandated by NRI Law Number 22 of 2022 Article 50, that the right to education of fostered children includes three types, namely formal, non-formal, and informal education. Instead, LPKA Class II Pangkalpinang provides non-formal education programs Package A, B, and C in collaboration with SKB. This package school is scheduled on Tuesdays, Wednesdays and Thursdays. In addition to intellectual education, the fostered children are given informal education in the form of religious education and independence. In order for the education program at LPKA to be more effective, efforts are needed such as improving the quality of teaching, both from educators and methods, as well as the duration of learning.